Applicability and Durability of Valve-Sparing Tetralogy of Fallot Repair. Issue 5 (October 2021) - Stephens, Elizabeth H.; Wolfe, Brian L.; Talwar, Abhinav A.; Patel, Angira; Camarda, Joseph A.; Eltayeb, Osama; Monge, Michael C.; Forbess, Joseph M.
Background: Although valve-sparing repair remains ideal for patients with tetralogy of Fallot, the durability of valve-sparing repair and which patients may have been better served with a transannular patch remain unclear. Methods: Retrospective review was performed of tetralogy of Fallot operations at our institution from January 2008 to December 2018. Standard demographic data were collected, including echocardiographic parameters, operative details, and clinical outcomes. Statistical analysis was performed comparing the transannular patch and valve-sparing repair groups. Results: Sixty-seven patients underwent tetralogy of Fallot repair with a median age of 4.5 (3.2-6.0) months and weight of 5.8 (5.2, 6.7) kg. Seventeen (25%) patients underwent transannular patch repair and 50 (75%) patients underwent valve-sparing repair. There was no difference in age or weight between patients who underwent a transannular patch repair and those who underwent a valve-sparing repair. At last follow-up (median 42 months), there was a trend of a higher peak pulmonary valve/right ventricular outflow tract gradient ( P = .06) in the valve-sparing group, but no difference in the pulmonary valve annulus z -scores. Additionally, the pulmonary valve z -scores in the valve-sparing group decreased from −2.3 ± 1.0 on predischarge echocardiogram of to −1.2 ± 1.6 on last follow-up, with the peak gradient on predischarge 23 (0-37) mm Hg remaining stable on last follow-up at 18 (0-29) mm Hg. There was one reoperation: pulmonary valve replacement six years after a transannular patch. Conclusions: Obtaining a postrepair pulmonary valve z -score of −2 yields satisfactory, stable valve-sparing repair with pulmonary valve growth, acceptable gradients, minimal regurgitation, and high freedom from reintervention during follow-up.